Highly Diastereoselective Synthesis of Polycyclic Indolines through Formal [4+2] Propargylic Cycloaddition of Indoles with Ethynyl Benzoxazinanones - Shao, Wen; Xu‐Xu, Qing‐Feng; You, Shu‐Li (Chemistry, an Asian journal, 2020)
A formal [4+2] propargylic annulation of indoles and pyrrole with ethynyl benzoxazinanones was described. This protocol provides a concise synthesis of tetrahydro‐5H‐indolo[2,3‐b]quinolines and tetrahydro‐3H‐pyrrolo[3,2‐b]quinoline, the core structures of alkaloid frameworks, featuring excellent yields, high diastereoselectivity, mild conditions and wide substrate scope. A metal‐free formal [4+2] propargylic cycloaddition between aza‐oQMs, which is in situ generated from ethynyl benzoxazinanones assisted by a common Brønsted base, and simple indole derivatives has been developed. This method provides a convenient and practical access to a variety of single diastereoisomeric polycyclic indolines in excellent yields under open‐flask ambient conditions.